1998
DOI: 10.1086/301977
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Structure and Population Genetic Inferences from Nucleotide-Sequence Variation in Human Lipoprotein Lipase

Abstract: Allelic variation in 9.7 kb of genomic DNA sequence from the human lipoprotein lipase gene (LPL) was scored in 71 healthy individuals (142 chromosomes) from three populations: African Americans (24) from Jackson, MS; Finns (24) from North Karelia, Finland; and non-Hispanic Whites (23) from Rochester, MN. The sequences had a total of 88 variable sites, with a nucleotide diversity (site-specific heterozygosity) of .002+/-.001 across this 9.7-kb region. The frequency spectrum of nucleotide variation exhibited a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
237
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(262 citation statements)
references
References 67 publications
23
237
2
Order By: Relevance
“…Experimental determination of ambiguous phase by allele-specific amplification can dramatically improve phasing, even when limited to a small number of SNP pairs and individuals [Clark et al, 1998]. Unfortunately, this method is not suitable for large-scale studies because experiments are individually designed along the phasing process, the technique is methodologically complex, and careful interpretation of agarose gels post-PCR is required.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental determination of ambiguous phase by allele-specific amplification can dramatically improve phasing, even when limited to a small number of SNP pairs and individuals [Clark et al, 1998]. Unfortunately, this method is not suitable for large-scale studies because experiments are individually designed along the phasing process, the technique is methodologically complex, and careful interpretation of agarose gels post-PCR is required.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have reported that the genome can be divided into blocks defined by LD between pairs of marker in a range from 5 to 100 kb with population differences in the extension. 42,54,55,57,67,68 Most of these studies report LD data for markers spanning large genomic regions, and used pre-ascertained SNPs from public databases with limited marker density. 56,[69][70][71] The identification of smaller blocks within candidate genes is probably beyond the resolution of these studies because of inadequate marker density for detection of LD patterns.…”
Section: Discussionmentioning
confidence: 99%
“…54 Overall, there were more estimated haplotypes in subjects of African ancestry. [55][56][57] In all, 31 haplotypes were population specific, with the highest number in AA (Table 3). The wild-type 'secretor haplotype' LYPA did not lie on a unique locus-wide haplotype.…”
mentioning
confidence: 97%
“…However, both the presence of blocks and the use of tagSNPs as markers for disease genes are controversial. 26,27 Moreover, tag-SNPs identified in one population may not be applicable to other populations 28 even if they seem to be quite general for Europeans. 29 Furthermore, Crawford et al, 30 after analyzing the sequence diversity in 100 human genes, concluded that the amount of LD and the haplotype structure should be empirically analyzed in order to assess which and how many SNPs must be typed in a specific gene to detect an association with a disease-causing SNP in a case-control study.…”
Section: Introductionmentioning
confidence: 99%